DEVELOPMENT OF ARTIFICIAL INTELLIGENCE TECHNOLOGY AND ITS INFLUENCE ON THE LEGAL FIELD - Kusumawardani, QD (SMART: Journal of Multidisciplinary Educational, 2023)
The era of industrial revolution 4.0. placing human life on faster technology. This era gave rise to changes in research paradigms driven by the communications technology revolution, economic globalization, changes in the legal profession and legal education. Artificial intelligence technology is making an impact in the legal field. The influence of artificial intelligence technology in the legal field is that this technology can help resolve legal problems by conducting analysis and review of large data sets (big data). Applications that use artificial intelligence technology in the legal field such as the Bloomberg points of law application, westlaw edge citator Improvement, cara on casetext, lex machina on lexis advance, judicata, ravel law, kira system, leverton, ebrevia, thoughtriver, lawgeex, legal robot, forever, ross intelligence